2016
DOI: 10.1364/oe.24.008679
|View full text |Cite
|
Sign up to set email alerts
|

Laser dynamical reservoir computing with consistency: an approach of a chaos mask signal

Abstract: We numerically investigate reservoir computing based on the consistency of a semiconductor laser subjected to optical feedback and injection. We introduce a chaos mask signal as an input temporal mask for reservoir computing and perform a time-series prediction task. We compare the errors of the task obtained from the chaos mask signal with those obtained from other digital and analog masks. The performance of the prediction task can be improved by using the chaos mask signal due to complex dynamical response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
99
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(102 citation statements)
references
References 31 publications
1
99
0
2
Order By: Relevance
“…Fast chaotic laser outputs have been used for applications in fast physical random number generation [16][17][18], secure key distribution [19,20], and reservoir computing [21,22]. Figure 1 shows the decision-making scheme based on the TOW method using chaotic temporal waveforms of the semiconductor laser.…”
Section: Tug-of-war Methods Using a Chaotic Semiconductor Lasermentioning
confidence: 99%
“…Fast chaotic laser outputs have been used for applications in fast physical random number generation [16][17][18], secure key distribution [19,20], and reservoir computing [21,22]. Figure 1 shows the decision-making scheme based on the TOW method using chaotic temporal waveforms of the semiconductor laser.…”
Section: Tug-of-war Methods Using a Chaotic Semiconductor Lasermentioning
confidence: 99%
“…A similar system was also employed to demonstrate highspeed optical vector and matrix operations [69]. Numerical simulations of this kind of system suggest that the information processing capabilities can still be improved by either increasing the injection strength [70] or by changing the input mask [71].…”
Section: All Optical Delay-based Reservoir Computingmentioning
confidence: 99%
“…In those implementations, the nonlinear response of the reservoir is provided by passive nonlinearity such as saturable absorption of a semiconductor mirror [9][10][11] or by active devices such as optoelectronic modulators [5,8], optical amplifiers [3], or semiconductor lasers [7]. These experiments have been supported by numerical simulations [8,[12][13][14][15]. Numerical simulations also have shown that the different modes of multimode lasers subject to optical delayed feedback can be used independently to process independent tasks in parallel [16].…”
mentioning
confidence: 99%
“…(ii) In the usual procedure of RC, the injection times of the input data (i.e., the inverse of the processing speeds) are close or correspond to the time delay. In addition, in previous experiments, long time delays (time delays much larger than the system's characteristic time) have been used [4][5][6][7][8][9][10][11][12][13][14]16]. We explore here whether time delays less than or comparable to the laser relaxation time can also be suitable for RC systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation